Cyclophosphamide‐hydroxycamptothecin as second‐line chemotherapy for advanced Ewing's sarcoma: Experience of a single institution. Issue 2 (26th November 2012) - Han, Kun; Sun, Yuanjue; Zhang, Jianjun; He, Aina; Zheng, Shui'er; Shen, Zan; Yao, Yang
Abstract Aim To investigate the feasibility and efficacy of cyclophosphamide (CTX)‐hydroxycamptothecin (HCPT) as second‐line chemotherapy on advanced Ewing's sarcoma. Methods From April 2009 to November 2010, 27 patients with advanced Ewing's sarcoma who had progressive disease after the first‐line chemotherapy regimen of vincristine, dactinomycin and cyclophosphamide and ifosfamide and etoposide were retrospectively reviewed in this analysis. CTX was given (0.6 g/m2, i.v. push day 1) and HCPT (6 mg/m2, i.v. drip days 1–5) as second‐line chemotherapy every 3 weeks. The primary end‐point was overall response rate, the secondary end‐point included progression‐free, overall survival, disease control rate and toxicities. Results A total of 134 cycles were given, median four cycles per patient (range 2–6). Overall response rate was 30% and disease control rate was 82%, with two complete response (8%), six partial remission (22%) and 14 stable disease (52%). The median time to progression and overall survival time were 7 months (95% CI 3–10) and 11 months (95% CI 5–18), respectively. Major severe toxicities (grade 3 and 4) were: nausea/vomiting (17%), alopecia (17%); leukopenia (27%) in total cycles. Mild toxicities (grade 1 or 2) were leukopenia (73%), nausea/vomiting (83%), hepatic lesion (14%) and anemia (44%). Conclusion A CTX‐HCPT regimen can control disease progression effectively and the side effects can be tolerable for Chinese advanced Ewing's sarcoma patients. Further assessment is necessary to confirm the safety and efficacy of this treatment.